A case of tumor-induced osteomalacia masked by acute kidney injury. Issue 2 (June 2023) - Kanduri, Swetha Rani; Kovvuru, Karthik; Wickman, Terrance J; Velez, Juan Carlos Q
Introduction: Hypophosphatemia in patients with tumor-induced osteomalacia (TIO) is due to abnormal excess production of fibroblast growth factor 23 (FGF-23) causing urinary phosphate wasting. However, in patients with coexisting acute kidney injury (AKI), hypophosphatemia may not be apparent as AKI reduces filtration and excretion of phosphate. Case report: We describe a case of 36-year-old woman who presented with right-sided abdominal pain. Initial laboratory testing revealed non oliguric AKI with creatinine (Cr) of 2.0 mg/dL (baseline 1.2 mg/dL), low phosphate (1.8 mg/dL), and normal parathyroid (PTH) levels. Hypophosphatemia in the setting of AKI and normal PTH raised suspicion for renal phosphate wasting disorder independent of PTH, triggering an order for FGF-23 level. Further into hospital stay, the AKI worsened (Cr rose to 7.2 mg/dL) and phosphate levels increased to 6.7 mg/dL casting doubt on the initial suspicion. However, FGF-23 level resulted at 12, 715 RU/mL, strongly suggesting TIO. Random liver biopsy was obtained as part of TIO work up due to liver ultrasound findings of hepatomegaly, diffuse parenchymal heterogenicity mimicking steatosis and potential ill-defined mass. Liver specimen showed tumor cells positive for CD56 and Ki-67, indicating high-grade metastatic neuro endocrine tumor which was the likely source of FGF-23. Patient rapidly deteriorated and opted for comfort measures. Conclusion: TIO typically manifests with overt hypophosphatemia. This case highlights the fact that decreased glomerular filtration rate may mask the degree of urinary phosphate wasting resulting in normal to high serum phosphate level. This warrants high index of suspicion to diagnose an underlying phosphate wasting disorder in the setting of normal to high serum phosphate levels and reduced kidney function.